Retinoblastoma in a 37 years old man in Nepal: A case report - Shrestha, A; Adhikari, RC; Saiju, R (Kathmandu University Medical Journal, 2010)
Retinoblastoma is extremely rare in adults. We report a case of Retinoblastoma diagnosed by histopathology in an enucleated specimen of a 37 year old patient who presented with pain and diminished visual acuity with intraocular mass and serous detachment. CT head and orbit showed uniform hyperdense mass in nasal quadrant of left globe projecting into adjacent vitreous cavity. Chest X Ray and USG abdomen was unremarkable. Initially provisional diagnosis of amelanotic melanoma was made. In view of nil visual prognoses enucleation was done. Sections from the enucleated eyeball showed diffuse proliferation of tumour cells. These tumour cells were small sized with scanty cytoplasm, and oval and hyper chromatic nuclei. A diagnosis of poorly differentiated Retinoblastoma was made with TNM (AJCC) stage as T1NXMX. This paper highlights the delayed presentation of retinoblastoma in adult. Although retinoblastoma is rare in adult, we suggest keeping retinoblastoma in differential diagnosis of intraocular mass until proven histopathology report is available. Key words: Retinoblastoma; Adult; Intraocular mass DOI: 10.3126/kumj.v8i2.3569 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 247-250